A reflection on the rooibos tea industry: empty tea bags - Peek, Molly, author (Colorado State University. Libraries, 2024)
Tea is a popular beverage enjoyed by tea drinkers in all corners of the globe. There are many variations including green, black, white, and herbal, among hundreds of others, all of which contain special ingredients sourced from global regions. While a great deal of tea ingredients are grown across Asia, specifically in India and China, specific roots, leaves, and spices are also found in South America and Africa. One such plant, known as Rooibos, is uniquely found only within a specific region within South Africa, called the Cederberg Region. With the entire supply of this plant concentrated in just one region, there are concerns about the protection and longevity of the rooibos crops. When a global supply comes all from just one place, forming a bottleneck, there are several complex sourcing issues that could arise if that supply is diminished. This foundational document will focus on the rooibos industry, how it is grown and harvested, the environmental, economic, and social concerns related to rooibos and South Africa, and ongoing solutions to these challenges. In addition to this foundational document, my thesis is presented in a visual medium, a world map created out of recycled tea bags. The piece highlights the scale of the globe compared to the small land area from which rooibos originates. It is also made using sustainable materials, highlighting the importance of global sustainability initiatives. I chose to produce a fine arts project for my thesis because I believe that the visual medium is an approachable way to introduce and represent complex issues. Current research in the art field has shown that contemporary art today, more than ever, is a catalyst for activism and political identification (Strehovec, 2020). The rooibos industry is plagued by several challenges, one being recognition. A visual representation of industry challenges via the tea map allows viewers to find intrigue in an industry and learn about something that they may not have encountered previously. I think that the interconnections of business, art, and social science in this piece make it approachable to a wide audience, prompting thought and curiosity on a multi-faceted situation.
University Honors Program, College of Business, Colorado State University. HONR499: Honors Thesis, Advisor: Dr. John Macdonald, Committee Members: Dr. Sara Bombaci & Dr. Tiffany Trzebiatowski. Fall 2024.
Keywords: rooibos; traditional ecological knowledge (TEK); global supply chain; climate change; fine arts project